Covid-19 : time for emergency G20 summit - Rana, Pradumna B. (2020)
The ever-growing toll of the COVID-19 pandemic has led to a growing sense of helplessness and loss of confidence worldwide. Coordinated global responses and action plans, together with a clear statement of solidarity from an Emergency G20 Summit could go a long way in reducing these fears.